The Influence of Transformational Leadership and Teacher Work Culture on Teacher Performance - Maman Herman; Lilis Kholisoh; Asep Ahmad Rifa’i (Syntax Corporation Indonesia, 2021)
The purpose of this study is to analyze and examine the influence of the principal's transformational leadership on teacher performance, the effect of teacher work culture on teacher performance, and the influence of principal transformational leadership and teacher work culture on teacher performance. This research method is descriptive quantitative. The data collection techniques are observation and questionnaires to 56 teachers/respondents. The data analysis technique is carried out through regression correlation analysis with statistical data processing of SPSS 17.0. The results show that the principal's transformational leadership in SMA Sariwangi District, Tasikmalaya Regency, is in the high criteria. The hypothesis testing results indicate that the principal's transformational leadership has a positive effect on teacher performance. The more effective the transformational leadership of the principal, the more teacher performance increases. Second, the work culture of teachers in SMA Sariwangi District, Tasikmalaya Regency is in high criteria. The results of hypothesis testing indicate that teacher work culture has a positive effect on teacher performance. The higher the work culture of the teacher, the higher the teacher's performance. Third, teachers' performance in SMA Sariwangi District, Tasikmalaya Regency, is generally at high criteria. The hypothesis testing results indicate that the principal's transformational leadership and teacher work culture positively influence teacher performance. It means that the more influential the principal's transformational leadership is and the higher its work culture, the more teacher performance increases.